Management of municipal solid waste and sustainable development - Coacalla-Castillo, Carlos-Enrique; Castro-Pérez, Gladys-Marilú; Santa-Cruz, Karla-Sadith; Torres-Chipana , Amalia; Callalli-Merino, Svetlania (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research presented at the Hermilio Valdizán National University, whose general objective was to determine the relationship between integrated solid waste management and sustainable development. It was developed through basic research, with a quantitative approach, within a non-experimental cross-sectional and correlational-level design. The population under study was the entire city of Abancay (Perú), which according to the 2017 census is 72,277 inhabitants, based on these data a non-probabilistic sampling was carried out, determining a sample of 246 inhabitants. To obtain the data, two questionnaires were prepared, one for each variable. The data was processed using non-inferential and inferential statistical processes. To test the hypotheses, the chosen test was Kendall’s Tau_b correlation coefficient, the inferential results allowed us to conclude that as municipal solid waste management is more appropriate, sustainable development will be better in the city. Because the p value (.000) < α=.05. The Tau_b coefficient = .638 determines that the degree of relationship between the variables is moderate.